Relations between morphological variables and normal and pathological conative characteristics of handball players - Stankovic, V.; Malacko, J.; Bojic, I.; Ilic, J. (SportLogia, 2013)
The aim of the research was to study the relations between morphological, normal and pathological conative characteristics of handball players of the Premiere Handball League of Serbia. The study was based on a system of 51 variables (23 anthropometric, 16 normal conative and 12 pathological conative variables). The data were collected on a suitable sample (N=71) and processed using a canonical correlation analysis. The results indicate that there is a canonical correlation between the systems of anthropometric variables and the system of normal conative characteristics (Rc=.80; p<.00), and that there were two statistically significant correlations between the system of normal and pathological conative characteristics (Rc=.69; p<.00 i Rc=.62; p<.02). The handball players of the ectomesomorph type are characterized at the one end with longitudinal measures and on the other with transversal dimensionality, the volume of the femoral region if they have increased values of conative variables, are extrovert and non-anxious. Among the handball players who are polite and considerate of each other there is an increase in the scores for depression as well as those which indicate a more pronounced vivacity and impulsiveness and expressiveness. Handball players who more frequently manifest dominant, competitive or even aggressive behavior are more anxious, while those who are more moral and adhere more to the rules are more prone to hypersensitivity. The ones who are undaunted and have an adventurous spirit score higher for obsession. Tense, energetic and impatient handball players often develop gastrointestinal conversion, hypochondria and phobias.